2010
DOI: 10.1007/s10462-010-9196-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal acoustic communication in human-computer interaction

Abstract: Nonverbal communication helps to compensate many hidden meanings omitted from spoken language. In some situations, nonverbal communication may even take the place of verbal communication. In this paper, we introduce how nonverbal acoustic communication can be utilized in human-computer interaction. We first overview acoustic techniques for nonverbal communication. Then we provide a design framework of nonverbal communication based intelligent agents. We demonstrate an example of the design using an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This corroborates what Maturana and D'Ávila (2015) said about the type of relational space that builds more and better conditions for human beings to become more collaborative with each other and manage to develop in living with others. Therefore, the improvement in communicational skills provided by the training which were expressed through the change in communication elements identified in the categories found, such as body posture, facial expression, speech, voice, emotions, and attention (WEIL; TOMPAKOW, 2015; NAVARRO, 2021;CHUN, 2000;NAVARRO, 2011;LIN;MAKEDON, 2010), reflected in the improvement of school managers' professional interactions with students' parents and with their collaborators. These results align with previous studies (OGAWA; FILIPAK, 2013; VERMA; PANDE, 2016), which indicated that developing communicational skills would improve managers' interactions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This corroborates what Maturana and D'Ávila (2015) said about the type of relational space that builds more and better conditions for human beings to become more collaborative with each other and manage to develop in living with others. Therefore, the improvement in communicational skills provided by the training which were expressed through the change in communication elements identified in the categories found, such as body posture, facial expression, speech, voice, emotions, and attention (WEIL; TOMPAKOW, 2015; NAVARRO, 2021;CHUN, 2000;NAVARRO, 2011;LIN;MAKEDON, 2010), reflected in the improvement of school managers' professional interactions with students' parents and with their collaborators. These results align with previous studies (OGAWA; FILIPAK, 2013; VERMA; PANDE, 2016), which indicated that developing communicational skills would improve managers' interactions.…”
Section: Discussionmentioning
confidence: 98%
“…The way human beings behave is directly connected to their communication skills structure, which belongs to the behavioral development scope and is associated with verbal and non-verbal communication (GUIMARÃES;FILIPKOWSKI, 2021). In verbal communication, elements such as speech and tone of voice are considered, whereas in non-verbal communication, factors such as body posture and emotional expressions (NAVARRO, 2011;COSENZA;GUERRA, 2011;NAVARRO, 2021;WEIL;TOMPAKOW, 2015;PEASE;PEASE, 2005;CHUN, 2000;LIN;MAKEDON, 2010).…”
Section: Introductionmentioning
confidence: 99%